The Impact of One Carbon Metabolism on Histone Methylation - Serefidou, Magdalini; Venkatasubramani, Anuroop Venkateswaran; Imhof, Axel (Frontiers in Genetics, 2019)
The effect of one carbon metabolism on DNA methylation has been well described, bridging nutrition, metabolism, and epigenetics. This modification is mediated by the metabolite S-Adenosyl Methionine (SAM), which is also the methyl-donating substrate of histone methyltransferases. Therefore, SAM levels that are influenced by several nutrients, enzymes, and metabolic co-factors also have a potential impact on histone methylation. Although, this modification plays a major role in chromatin accessibility and subsequently in gene expression in healthy or diseased states, its role in translating nutritional changes in chromatin structure has not been extensively studied. Here, we aim to review the literature of known mechanistic links between histone methylation and the central one carbon metabolism.